2021
DOI: 10.1007/s12031-021-01936-1
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Ameliorates Cognitive Deficits in Streptozotocin Murine Model of Sporadic Alzheimer’s Disease via Attenuation of Oxidative Stress, Inflammation, and Mitochondrial Dysfunction

Abstract: Intracerebroventricular (ICV) microinjection of diabetogenic drug streptozotocin (STZ) in rodents consistently produces a model of sporadic Alzheimer's disease (sAD) which is characterized by tau pathology and concomitant cognitive decline, insulin resistance, neuroinflammation, oxidative stress, and mitochondrial malfunction. Paeonol is an active phenolic component in some medicinal plants like Cortex Moutan with neuroprotective efficacy via exerting anti-inflammatory and antioxidative effects. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…Paeonol has been shown to be able to inhibit oxidative stress-induced neuronal damage and microglia-mediated inflammation, to mediate the RhoA/Rock2 pathway, attenuating the loss of neuronal dendritic spines and to increase the frequency of spontaneous excitatory postsynaptic currents and miniature excitatory postsynaptic currents . Paeonol has also been found to inhibit the impairment of AD related behaviors in animal models. Our results on paeonol have not only verified the compound’s AD-related activities, revealing more details regarding its molecular/cellular mechanism, but we have also showed that the compound has efficacy on our platform to prevent Aβ-induced depolarization. After modification of the structure of paeonol by adding methyl/hydroxyl groups, 6′-methyl paeonol is more effective than paeonol on the AMPA-induced abnormalities present in primary neurons.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Paeonol has been shown to be able to inhibit oxidative stress-induced neuronal damage and microglia-mediated inflammation, to mediate the RhoA/Rock2 pathway, attenuating the loss of neuronal dendritic spines and to increase the frequency of spontaneous excitatory postsynaptic currents and miniature excitatory postsynaptic currents . Paeonol has also been found to inhibit the impairment of AD related behaviors in animal models. Our results on paeonol have not only verified the compound’s AD-related activities, revealing more details regarding its molecular/cellular mechanism, but we have also showed that the compound has efficacy on our platform to prevent Aβ-induced depolarization. After modification of the structure of paeonol by adding methyl/hydroxyl groups, 6′-methyl paeonol is more effective than paeonol on the AMPA-induced abnormalities present in primary neurons.…”
Section: Discussionsupporting
confidence: 62%
“…The half maximal inhibitory concentration (IC 50 ) of paeonol based on the survival of glutamatergic neurons can not be determined thus far because the drug seems to have no effect even at 1 mM (Figure B). The effect of paeonol on AD has not been studied to a great extent and what research there is has mainly focused on its antioxidant effects ,, and effects at the organism level . We investigated this compound further by creating derivatives in addition to exploring its mechanism of action in more detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of anti‐neuronal apoptosis, Pae inhibited the expression of caspase‐3 in the hippocampus and cortex of model rats and also restored the expression of BDNF and insulin‐like growth factor 1 (IGF‐1) to play a protective role in cognitive function (Liu, Feng, et al, 2013). Pae can reduce the levels of MDA and ROS in hippocampus and downregulate the proinflammatory factors myeloperoxidase (MPO), TNF‐α and IL‐6 expression in AD rats caused by diabetes, and the inhibition of astrocyte proliferation (Tayanloo‐Beik et al, 2022). In terms of improving diabetes, Pae prevented the weight loss of model rats, and high‐dose Pae reduced the blood sugar level and the content of advanced glycation end products, their receptors and glycosylated serum protein in DE rats, but the effect was not as good as the positive control drug aminoguanidine.…”
Section: Protective Effect Of Pae On Cnsmentioning
confidence: 99%
“…The dysfunctional metabolism of blood glucose damages the basilar membranes of capillaries leading to a narrowed cavity in the cerebra, thus decreasing blood supply to the brain and resulting in oxygen-free radical injury [21]. Oxidative stress is observed in cognitive impairment by increased levels of reactive oxygen species (ROS) and malondialdehyde (MDA), and decreased phase II antioxidant enzymes activities of glutathione peroxidase (GPx), chloramphenicol acetyltransferase (CAT) and superoxide dismutases (SOD) [22,23]. The brain is highly susceptible to such oxidative damage partially due to its high oxygen demand, and the fact that high amounts of polyunsaturated fatty acids are easily targeted by free radicals [24].…”
Section: Introductionmentioning
confidence: 99%